2018
DOI: 10.1088/1748-3190/aa8f6a
|View full text |Cite
|
Sign up to set email alerts
|

How mimetic should a robotic fish be to socially integrate into zebrafish groups?

Abstract: Biomimetic robots are promising tools in animal behavioural studies. If they are socially integrated in a group of animals, they can produce calibrated social stimuli to test the animal responses. However, the design of such social robots is challenging as it involves both a luring capability including appropriate robot behaviours, and the acceptation of the robots by the animals as social companions. Here, we investigate the integration of a biomimetic robot driven by biomimetic behavioural models into a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(79 citation statements)
references
References 42 publications
0
76
0
Order By: Relevance
“…It also confirms the hypothesis that 'bold' behaviour is sufficient to explain the variations observed in the distribution of leadership of Danio rerio. This conclusion goes further than our previous work with autonomous robots [14], [30], [15]. Indeed, the initiations of collective departures have never been explicitly simulated by a fish robot before.…”
Section: Discussionmentioning
confidence: 66%
“…It also confirms the hypothesis that 'bold' behaviour is sufficient to explain the variations observed in the distribution of leadership of Danio rerio. This conclusion goes further than our previous work with autonomous robots [14], [30], [15]. Indeed, the initiations of collective departures have never been explicitly simulated by a fish robot before.…”
Section: Discussionmentioning
confidence: 66%
“…It is them analysed to track the fish positions. Experiments were carried out with 10 groups of 5 adult (6-12 months old) wild-type AB zebrafish (Danio rerio) in ten 30-minutes trials as in [6], [29]. Experiments conduced in this study were performed under the authorisation of the Buffon Ethical Committee (registered to the French National Ethical Committee for Animal Experiments #40) after submission to the French state ethical board for animal experiments.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Moreover, the design of such social robots is challenging as it involves both a luring capability including appropriate robot behaviours, and the social acceptation of the robots by the animals. We have shown that the social integration of robots into groups of fish can be improved by refining the behavioural models used to build their controllers [8]. The models have also to be calibrated to replicate accurately the animal collective behaviours in complex environments [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research on animal and robot interactions need also bio-mimetic formal models as behavioural controllers of the robots if the robots have to behave as congeners [3], [2]. Robots controllers have to deal with a whole range of behaviours to allow them to take into account not only the other individuals but also the environment and in particular the walls [8], [7]. However, most of biological collective behaviour models deal only with one sub-part at a time of fish behaviours in unbounded environments.…”
Section: Introductionmentioning
confidence: 99%